Stadial-Interstadial Temperature and Aridity Variations in East Central Europe Preceding the Last Glacial Maximum - Bernasconi, Stefano M.; id_orcid:0 000-0001-7672-8856; Újvári, Gábor; Stevens, Thomas; Kele, Sándor; Páll-Gergely, Barna; Surányi, Gergely; Demény, Attila (Paleoceanography and Paleoclimatology, 2021)
ISSN:2572-4525 ISSN:2572-4517